2020
DOI: 10.15252/msb.20209819
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics identifies microglial Siglec‐F inflammatory response during neurodegeneration

Abstract: Alzheimer’s disease (AD) is characterized by the appearance of amyloid‐β plaques, neurofibrillary tangles, and inflammation in brain regions involved in memory. Using mass spectrometry, we have quantified the phosphoproteome of the CK‐p25, 5XFAD, and Tau P301S mouse models of neurodegeneration. We identified a shared response involving Siglec‐F which was upregulated on a subset of reactive microglia. The human paralog Siglec‐8 was also upregulated on microglia in AD. Siglec‐F and Siglec‐8 were upregulated foll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 121 publications
(166 reference statements)
1
18
0
Order By: Relevance
“…Aberrant phosphorylation, such as the hyperphosphorylation of tau protein, plays a key role in AD pathology ( Bai et al., 2020 ; Morshed et al., 2020 ; Perluigi et al., 2016 ; Zhang et al., 2019 ). Thus, in order to support the insights obtained in our WGCNA, we subsequently conducted a phosphoproteomics study of the spinal cord, which presented the most severe tau-induced neuronal damage.…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant phosphorylation, such as the hyperphosphorylation of tau protein, plays a key role in AD pathology ( Bai et al., 2020 ; Morshed et al., 2020 ; Perluigi et al., 2016 ; Zhang et al., 2019 ). Thus, in order to support the insights obtained in our WGCNA, we subsequently conducted a phosphoproteomics study of the spinal cord, which presented the most severe tau-induced neuronal damage.…”
Section: Resultsmentioning
confidence: 99%
“…Mice do not express Siglec-8, but Siglec-F is a likely functional orthologue of Siglec-8. Siglec-F was upregulated on a subset of reactive microglia in models of neurodegeneration, and it was observed that Siglec-F is dependent on Aβ deposition at early AD stages [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Morshed et al identified signaling pathways that were dysregulated in various mouse models of AD using quantitative phosphoproteomics and found that Siglec-F was upregulated as a shared response in a subset of reactive microglia [ 114 ]. The levels of the human paralog, Siglec-8, were also increased in aged human microglia and in the microglia of patients with LOAD [ 114 ]. Previous studies showed Siglec-F is an eosinophil surface receptor, and Siglec-8 is expressed by human eosinophils.…”
Section: Clues To the Pathogenesis Of Ad Based On “Omics” Analysis Re...mentioning
confidence: 99%
“…Genetic knockout of Siglecf lead to increased inflammation in asthma [ 115 ], indicating that Siglec-F mediated an immune response. An in vitro study showed that both Siglec-F and Siglec-8 were upregulated following microglial activation, and Siglecf overexpression activated an endocytic and pyroptotic inflammatory response in BV-2 cells, a mouse microglial cell line [ 114 ]. The functions and mechanisms of Siglec-F and Siglec-8 are unclear; therefore, whether their upregulation on microglia during aging and AD are secondary to microglial activation, or whether they mediate microglial inflammatory pathways, requires further investigation.…”
Section: Clues To the Pathogenesis Of Ad Based On “Omics” Analysis Re...mentioning
confidence: 99%